Pengaruh Digital Marketing Mobile Application dan Service Quality terhadap Purchase Decision Pelanggan Transportasi Online Indrive - Putri Fatimah , Nadhifa Amelia; Saraswati, Septiana Ayu Estri Mahani, Nindya; Saraswati, Nindya (Bandung Conference Series: Business and Management, 2024)
Abstract. The Institute for Development of Economics and Finance (INDEF) survey results show that the service quality and digital marketing of Indrive's online transportation services are still low compared to other competitors. This can have an impact on customer purchasing decisions about the service. The purpose of this study is to ensure that Indrive's online transportation services work well and meet customer expectations and desires. This study uses a quantitative survey method to collect data from a defined population and sample. This is done using primary data and structured research instruments to test the hypothesis that has been set. There is an insignificant and negative influence between Digital Marketing Mobile Application and Purchase Decision. Meanwhile, in the Service Quality variable on Purchase Decision there is a positive and significant influence. And Digital Marketing Mobile Application and Service Quality simultaneously (together) affect Purchase Decision. From the research results, it is better for the Indrive company to improve in terms of digital marketing, both in terms of informative applications and various features, and in terms of services, to continue to improve the ability to provide the best and maximum service possible for its customers. so that it can create a sense of interest and user trust when going to use the services of Indrive. Abstrak. Hasil survei Institute for Development of Economics and Finance (INDEF) menunjukkan bahwa kualitas layanan dan pemasaran digital layanan transportasi online Indrive masih rendah dibandingkan dengan kompetitor lainnya. Ini dapat berdampak pada keputusan pembelian pelanggan tentang layanan tersebut. Tujuan dari penelitian ini adalah untuk memastikan bahwa layanan transportasi online Indrive bekerja dengan baik dan memenuhi harapan dan keinginan pelanggan. Studi ini menggunakan metode kuantitatif survei untuk mengumpulkan data dari populasi dan sampel yang ditentukan. Ini dilakukan dengan menggunakan data primer dan instrumen penelitian yang sudah terstruktur untuk menguji hipotesis yang telah ditetapkan. Terdapat pengaruh yang tidak signifikan dan negatif antara Digital Marketing Mobile Application dengan Purchase Decision. Sedangkan, pada variabel Service Quality terhadap Purchase Decision terdapat pengaruh yang positif dan signifikan. Dan Digital Marketing Mobile Application dan Service Quality secara simultan (bersama-sama) berpengaruh terhadap Purchase Decision. Dari hasil penelitian, ada baiknya perusahaan Indrive meningkat dalam hal digital marketing-nya baik secara aplikasi yang informatif maupun fitur yang beragam, dan dari segi layanannya, untuk meningkatkan terus kemampuan memberikan layanan yang terbaik dan semaksimal mungkin bagi para pelanggannya. sehingga dapat menciptakan rasa ketertarikan dan kepercayaan pengguna ketika akan menggunakan layanan dari Indrive.